Living Smart, Living Fit - J. Nwando Olayiwola; O. Corazon Irizarry; Kelli O'Connell; Stephanie Milan (SAGE Publishing, 2013)
Background: Depression and obesity/overweight during pregnancy are important public health concerns, as they are frequently associated with poor birth outcomes. The Living Smart, Living Fit® (LSLF) program was an intervention program initiated in 2008 to provide comprehensive care to low-income pregnant and postpartum women with elevated body mass index (BMI) and depressive symptoms. It linked patients to clinical care coordinators trained in motivational interviewing who promoted participation in a portfolio of mental and physical wellness activities. Objective: The objective of this study was to evaluate the effectiveness of LSLF in improving depression, BMI, birth weight, and smoking status among low-income perinatal patients. Methods: Women with Patient Health Questionnaire (PHQ-9) depression scores ≥10 and/or BMI >25 kg/m 2 at their prenatal intake visit were eligible for enrollment into the LSLF program. Enrolled participants met with clinical care coordinators who encouraged engagement in a portfolio of LSLF activities that included pregnancy/family, physical health, and mental health interventions. Outcomes were measured at the 6-week postpartum visit and included change in PHQ-9 scores, change in BMI, birth weight, and change in smoking status. Results: Of the 107 enrollees, 86% participated in some LSLF activity. Participation in pregnancy/family related activities was significantly associated with decreased PHQ-9 scores. Participation in mental health services was significantly associated with increased birth weight. No changes in BMI or smoking status were associated with LSLF involvement. Conclusions: The findings of this pilot study indicate that pregnant women with depression or obesity/overweight can benefit from care coordination and a portfolio of activities for mental and physical wellness. The LSLF program provides a model for delivering this patient-centered comprehensive support. Further research should include more controlled trials to better evaluate the effectiveness of LSLF intervention.